Molecular determinants of a competent bovine corpus luteum: first vs final wave dominant follicles - Gregson, Emma; Webb, Robert; Sheldrick, Elizabeth L.; Campbell, Bruce K.; Mann, George E.; Liddell, Susan; Sinclair, Kevin D. (Society for Reproduction and Fertility, 2016)
Reproductive management in cattle requires the synchrony of follicle development and oestrus before insemination. However, ovulation of follicles that have not undergone normal physiological maturation can lead to suboptimal luteal function. Here, we investigated the expression of a targeted set of 47 genes in (a) a first-wave vs final-wave dominant follicle (DF; the latter destined to ovulate spontaneously) and (b) 6-day-old corpora lutea (CLs) following either spontaneous ovulation or induced ovulation of a first-wave DF to ascertain their functional significance for competent CL development. Both the mass and progesterone-synthesising capacity of a CL formed following induced ovulation of a first-wave DF were impaired. These impaired CLs had reduced expression of steroidogenic enzymes (e.g. STAR and HSD3B1), luteotrophic receptors (LHCGR) and angiogenic regulators (e.g. VEGFA) and increased expression of BMP2 (linked to luteolysis). Relative to final-wave DFs, characteristic features of first-wave DFs included reduced oestradiol concentrations and a reduced oestradiol:progesterone ratio in the face of increased expression of key steroidogenic enzymes (i.e. CYP11A1, HSD3B1 and CYP19A1) in granulosa cells and reduced expression of the HDL receptor SCARB1 in thecal cells. Transcripts for further components of the TGF and IGF systems (e.g. INHA, INHBA, IGF2R and IGFBP2) varied between the first- and final-wave DFs. These results highlight the importance of hormones such as progesterone interacting with local components of both the TGF and IGF systems to affect the maturation of the ovulatory follicle and functional competency of the subsequent CL.